2018
DOI: 10.1007/s40430-017-0935-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heat transfer and pressure drop of turbulent flow in tubes with successive alternating wall deformation under constant wall temperature boundary conditions

Abstract: In this study, the effects of the presence of multi-longitudinal vortex and various rotation angles between the pitches of alternating elliptical axis (AEA) tubes on heat transfer and pressure drop of turbulent flow were numerically investigated. Turbulent flow of water fluid was simulated at Reynolds numbers of 10,000-60,000. The turbulent flow and heat transfer in the tubes were discussed in terms of parameters such as static pressure, velocity magnitude, wall shear stress, turbulent intensity, performance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Performance of the double corrugated tubes was compared to the AEA tubes reported by Khaboshan and Nazif, [13]. The latter tubes were modelled in the turbulent flow regime with constant temperature of the tube wall.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Performance of the double corrugated tubes was compared to the AEA tubes reported by Khaboshan and Nazif, [13]. The latter tubes were modelled in the turbulent flow regime with constant temperature of the tube wall.…”
Section: Resultsmentioning
confidence: 99%
“…The global performance of the double corrugated tubes was analysed using the most commonly adopted performance evaluation criterion PEC, which is defined by Eq. 16 [1,13].…”
Section: ℎ = ∆ (12)mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies on different augmented and/or coated surfaces [6], e.g., tubes with fitted inserts [9][10][11][12], grooved surfaces [13][14][15] and structured microchannels [16] have been reported. Various types of corrugations have been analysed as well; for instance, tubes with multiple starts [17], tubes with alternating ellipse axes [18,19] and double corrugated tubes with constant hydraulic diameter, D h , or constant cross-section area, A c , [20,21]. All of the reported numerical and/or experimental studies have demonstrated a significant increase in heat transfer inside the tube geometry with higher or lower increase in pressure drop compared to a baseline case.…”
Section: Introductionmentioning
confidence: 99%